Swamp Buffalo in South Kalimantan : Problem, Disease and Control - Natalia, Lily; ., Suhardono; Priadi, Adin (Indonesian Animal Sciences Society, 2006)
In recent years, several studies have been carried out to evaluate and investigate the important diseases of swamp buffaloes (Bubalus carabanensis) in Kalimantan . More attention has been focused on the case of acute infectious diseases and sudden death in the buffaloes . Fasciolosis black disease, acute enteritis, especially fatal enterotoxaemia haemorrhagic septicaemia . and trypanosomiasis (Surra), are some of the important diseases found in these animals . Black disease caused by toxigenic Clostridium novyi occurs in the presence of the organism in the liver and the degree of liver fluke Fasciola gigantica infestation . In regions where black disease is enzootic, Cl. novvi can be isolated from livers of normal healthy animals . In Hulu Sungai Utara district, South Kalimantan, the prevalence of fasciolosis caused by Fasciola gigantica in swamp buffalo was 77% in 1991 . A gross sudden change in diet due to seasonal changes could induce rumen and intestinal stasis, which provide a favourable environment for the rapid proliferation of commensal toxigenic Clostridium perfringens in the small intestine . Subsequent absorption of the toxin produced through the gut wall and its generalized dissemination culminated in a fatal enterotoxaemia . Haemorrhagic septicaemia (HS) is an acute, fatal disease affecting swamp buffalo, and caused by Pasteurella multocida B : 2 . The swamp buffalo is particularly susceptible for HS, and the reported greatest losses of swamp buffalo in Kalimantan due to HS is recorded in 1980s. The clinical signs of Surra in swamp buffalo were also found in certain areas in Danau Panggang area . Hulu Sungai Utara district . Vaccination is the accepted method for controlling Black disease, enterotoxaemia and HS. Multi component vaccine, alum adjuvant containing at least 5 types of clostridial toxoids and P. multocida B2 bacterin have been used and provide good protection to the animals . Control and treatment of liver fluke infestation is advisable. Vaccination is recommended annually and should be carried out regularly . In these days, the farmers concern about the availability of the grass in the Danau Panggang area . The primary feed grass (Oryza sativa forma spontanea L), of the swamp buffalo were not sufficient in the low-tide season. The over population of Pamocea canaliculata (golden snail), a pest for lake vegetations, was thought to be responsible for this phenomena . Growing forages as the source of animal feed may be an option to improve the current performance of the swamp buffalo in the area. Key words : Diseases, swamp buffalo, control, South Kalimantan